2019
DOI: 10.1016/j.ijnss.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-harm attempters’ perception of community services and its implication on service provision

Abstract: Objective This study aimed at exploring the attempters’ perception of community social services included any barriers to seeking help and services. Method The participants were patients with self-harming behavior aged 15 years or above. A set of guiding questions were designed to explore the general barriers and accessibility to community social services. A voice recording was made, which was later converted into a text transcript and then preceded for content analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In some studies ( 53 55 ), gambling itself was described as the generic cause of suicide. Leung et al ( 54 ) interviewed suicidal or self-harming individuals and found that pathological gambling was identified as one of the main contributing factors for self-harm. A case study of an individual in Estonia having committed familicide ( 55 ) found that the person had not exhibited suicidal behavior before commencing heavy gambling on electronic gambling machines (EGMs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies ( 53 55 ), gambling itself was described as the generic cause of suicide. Leung et al ( 54 ) interviewed suicidal or self-harming individuals and found that pathological gambling was identified as one of the main contributing factors for self-harm. A case study of an individual in Estonia having committed familicide ( 55 ) found that the person had not exhibited suicidal behavior before commencing heavy gambling on electronic gambling machines (EGMs).…”
Section: Resultsmentioning
confidence: 99%
“…Other life situation related issues appear to have rather stemmed from gambling or emerged after gambling had commenced. These related notably to interpersonal problems and relationship difficulties ( 36 , 53 , 54 ) or to problems at study or work ( 36 , 53 ). These are typically related to gambling debts and losses [also Blaszczynski and Farrell ( 36 )].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most individuals have health system contact prior to suicide, which means opportunities for suicide prevention in primary care or medical specialty settings (Ahmedani et al, 2014). Therefore, it is important to introduce various service changes related to ward safety, community services, training, and policy and guidance (Kapur et al, 2016; Leung, Chow, Ip, & Yip, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The point is how to create understanding and reframe the patient’s confidence in home visiting to be positive (Grant, 2015), and how to work with the community to reduce stigmatization in mental illness. Supporting the competency of community nurses can enhance the effectiveness of psychiatric care while providing primary care (Leung et al, 2019).…”
Section: Discussionmentioning
confidence: 99%